Proses untuk Menurunkan Konsentrasi Sianida Bebas dalam Air Limbah Pertambangan Emas Skala Kecil - Majalis, Asep Nurohmat; Lusiani, Sri; Novitasari, Yeni (Jurnal Teknologi Lingkungan, 2019)
ABSTRACTThe processing of gold by cyanidation has an impact on the release of free cyanide into the environment contained in the tailings. Free cyanide is very dangerous because it has very high toxicity. The process to remove free cyanide from tailings is the oxidation-precipitation using a mixture of sulfur and oxygen catalyzed by copper (II). This process can reduce the concentration of free cyanide as well as heavy metals. Free cyanide is oxidized to cyanate and heavy metals are deposited as metal-hydroxide. The optimum parameter of these methods on tailing cyanidation from gold ore Lebak Situ Village-Lebak Gedong District-Lebak Regency-Banten province are the ratio of the weight of SO2/CN- is 7; the catalyst dose is 75 mg/L; pH is 9 and the processing time is 4 hours. Application tests of the optimum parameter were able to reduce free cyanide concentration from 95.8 mg/L to 0.25 mg/L. Wastewater from the processing with this process has fulfilled the specified Quality Standards. The wastewater pollution index value before the treatment process is 136.32, changing to 0.36 after processing. These changes indicate that the oxidation-precipitation process has been able to change the condition of cyanidation wastewater from heavily polluted to better conditions.Keywords: cyanidation, tailing, oxidation, optimum parameter, aplication test, pollution index ABSTRAKPengolahan emas dengan sianidasi berdampak pada pelepasan sianida bebas ke lingkungan yang terkandung di dalam tailing. Sianida bebas sangat berbahaya karena mempunyai toksisitas yang sangat tinggi. Salah satu proses untuk menghilangkan sianida bebas dari tailing adalah oksidasi-presipitasi menggunakan campuran gas sulfur dan oksigen terkatalisis tembaga (II). Proses ini mampu menurunkan konsentrasi sianida bebas sekaligus logam berat. Sianida bebas dioksidasi menjadi sianat dan logam berat diendapkan sebagai logam-hidroksida. Parameter optimum proses tersebut pada tailing sianidasi bijih emas Lebak Situ Kecamatan Lebak Gedong Kabupaten Lebak Provinsi Banten adalah rasio berat SO2/CN- 7; dosis katalis 75 mg/L; pH pengolahan 9 dan waktu pengolahan 4 jam. Uji aplikasi parameter optimum tersebut mampu menurunkan konsentrasi sianida bebas dari 95,8 mg/L menjadi 0,25 mg/L. Air limbah hasil pengolahan dengan proses tersebut telah memenuhi Baku Mutu yang ditetapkan. Nilai indeks pencemaran air limbah sebelum proses pengolahan adalah 136,32 berubah menjadi 0,36 setelah dilakukan proses pengolahan. Perubahan tersebut menunjukkan bahwa proses oksidasi-presipitasi telah mampu mengubah kondisi air limbah sianidasi dari tercemar berat menjadi kondisi lebih baik.Kata kunci: sianidasi, tailing, oksidasi, parameter optimum, uji aplikasi, indeks pencemaran